Translation and linguistic validation into Spanish of the Owner-Reported Outcome Measure “Liverpool Osteoarthritis in Dogs” - Olcoz, María; Cabezas, Miguel Ángel; Gómez de Segura, Ignacio A. (Frontiers in Veterinary Science, 2024)
Introduction Assessing chronic pain in dogs has been greatly favoured by the development of Owner-Reported Outcome Measures. Among them, the Liverpool Osteoarthritis in Dogs (LOAD) has been widely used for this purpose. Most of these tools have been written in English and its use by non English natives requires not only translation but also linguistic validation for use by veterinarians and owners. For its use, the LOAD has not undergone translation into Spanish and the objective was to generate a linguistically validated Spanish translation of the LOAD. Methods Following the World Health Organisation and the International Society for Pharmacoeconomics and Outcomes Research published guidelines, the original LOAD English version underwent analysis and translation by two native linguists proficient in the target language. Both translations were then reviewed by a third native linguist to identify potential disparities and establish a cohesive translation (reconciliation). Subsequently, an independent linguist, fluent in both English and the target language, conducted the back translation. Finally, the research team compared the original and back translated versions to pinpoint and resolve any significant differences. Following the creation of the translated version, a cognitive debriefing was conducted to assess the questionnaire within the target population. Results A total of 89 surveys were distributed to dog owners of varying ages, genders, and socioeconomic backgrounds. Although there were some suggestions and comments, and some adjustments were made, all respondents found the survey to be clear, achieving a linguistic validation of the Spanish LOAD.